Réponses

2014-02-07T16:25:32+01:00
Bonjour

a = 2(x - 1) + 2(y + 2) - 2(1 + z)
  = 2x - 2 + 2y + 4 - 2 - 2z
  = 2x + 2y - 2z

b = 3x - (3 - 3y ) + 3(z + 1)
   = 3x - 3 + 3y + 3z + 3
   = 3x + 3y + 3z

c = (x + y -1) + (x + y + 1) - (x + y - z)
   = x + y - 1 + x + y + 1 - x - y + z
   = x + y + z

d = 2(x - y) + 3(y - z) + 4(z - x) + 3x
   = 2x - 2y + 3y - 3z + 4z - 4x + 3x
   = x + y + z

e = x(1 - y) + y(1 - z) + z(1 - x) + xy + yz +xz
   = x - xy + y - yz + z - xz + xy + yz + xz
   = x + y + z

f = (x + 2)(-x - 3) + 3x²
  = -x² - 3x - 2x - 6 + 3x²
  = 2x² - 5x - 6